2015
DOI: 10.4041/kjod.2015.45.5.226
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term treatment outcomes with Class III activator

Abstract: ObjectiveThe purpose of this retrospective study was to investigate short-term and long-term skeletodental outcomes of Class III activator treatment.MethodsA Class III activator treatment group (AG) comprised of 22 patients (9 boys, 13 girls) was compared with a Class III control group (CG) comprised of 17 patients (6 boys, 11 girls). The total treatment period was divided into three stages; the initial stage (T1), the post-activator treatment or post-mandibular growth peak stage (T2), and the long-term follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Studies have suggested that the posttreatment outcome of orthopedic treatment may not be stable depending on the residual growth. 76 When unfavorable growth is expected, treatment would not be initiated in the early phase or would be delayed until completion of growth, because a discrepancy between maxillary, mandibular, and skeletal base growth during the pubertal phase can result in relapse of the corrections which have been achieved earlier, 77 and as a result some patients ultimately may require orthognathic surgery at a later stage. This is a disappointing situation, not only for patients but also for clinicians, and may be prevented if accurate prediction of the eventual prognosis of early orthopedic treatment for skeletal Class III malocclusion would have been possible before commencing and executing treatment.…”
Section: Assessment Of Growth and Prognosis In Class III Patientsmentioning
confidence: 99%
“…Studies have suggested that the posttreatment outcome of orthopedic treatment may not be stable depending on the residual growth. 76 When unfavorable growth is expected, treatment would not be initiated in the early phase or would be delayed until completion of growth, because a discrepancy between maxillary, mandibular, and skeletal base growth during the pubertal phase can result in relapse of the corrections which have been achieved earlier, 77 and as a result some patients ultimately may require orthognathic surgery at a later stage. This is a disappointing situation, not only for patients but also for clinicians, and may be prevented if accurate prediction of the eventual prognosis of early orthopedic treatment for skeletal Class III malocclusion would have been possible before commencing and executing treatment.…”
Section: Assessment Of Growth and Prognosis In Class III Patientsmentioning
confidence: 99%
“…Esto fue estudiado en profundidad por Buschang, quien observó el crecimiento craneofacial de pacientes Clase III entre 6 y 16 años de edad, concluyendo que el crecimiento anteroposterior mandibular se va acumulando en el tiempo obteniendo como resultado, mandíbulas más grandes y prominentes (19) , lo que indicaría que la intercepción ortopédica temprana de esta maloclusion, juega un rol fundamental en la redirección favorable del crecimiento craneofacial. Si bien, el pronóstico del tratamiento ortopédico es favorable cuando el tratamiento se indica antes del peak de crecimiento puberal (20) , algunos autores han sugerido que el resultado posterior al tratamiento ortopédico puede no ser estable dependiendo del crecimiento residual (21) . Esta es una situación decepcionante y podría prevenirse si la predicción individual del pronóstico de tratamiento ortopédico, hubiera sido posible antes de comenzar y ejecutar el tratamiento.…”
Section: Discussionunclassified
“…A reliable reference landmark is an essential component of cephalometric analyses for orthodontic diagnosis, treat- ment planning, posttreatment evaluation, and anthropological studies. Many reference planes have been used, including the Frankfort horizontal plane, mid-sagittal plane, sellanasion plane, and facial plane [14]. Most of these planes are defined based on intracranial anatomical points, and the Frankfort horizontal plane has been the most widely used standard horizontal plane for reflecting the natural head position [4].…”
Section: Discussionmentioning
confidence: 99%